Behavioral and Gene Regulatory Responses to Developmental Drug Exposures in Zebrafish - Mech, Aleksandra M.; Merteroglu, Munise; Sealy, Ian M.; Teh, Muy-Teck; White, Richard J.; Havelange, William; Brennan, Caroline H.; Busch-Nentwich, Elisabeth M. (Frontiers in Psychiatry, 2022)
Developmental consequences of prenatal drug exposure have been reported in many human cohorts and animal studies. The long-lasting impact on the offspring - including motor and cognitive impairments, cranial and cardiac anomalies and increased prevalence of ADHD - is a socioeconomic burden worldwide. Identifying the molecular changes leading to developmental consequences could help ameliorate the deficits and limit the impact. In this study, we have used zebrafish, a well-established behavioral and genetic model with conserved drug response and reward pathways, to identify changes in behavior and cellular pathways in response to amphetamine, nicotine and oxycodone exposures during the first five days of development, a period equivalent to the first trimester of human fetal development. A range of behavioral assays showed changes in behavior consistent with mammalian systems, such as impaired locomotion, anxiety-like behavior and habituation in exposed animals in the presence of the drug. Contrasting evidence from acute exposure and short-term withdrawal suggest a mechanism of adaptation to the presence of the drug. Transcriptomic analysis of exposed larvae revealed differential expression of numerous genes and alterations in many pathways, including those related to cell death, immunity and circadian rhythm regulation. Differential expression of circadian rhythm genes did not correlate with behavioral changes in the larvae, however, two of the circadian genes, arntl2 and per2, were also differentially expressed at later stages of development, suggesting a long-lasting impact of developmental exposures on circadian gene expression. The immediate-early genes, egr1, egr4, fosab and junbb, which are associated with synaptic plasticity, are downregulated by all three drugs and in situ hybridization showed that the expression for all four genes was reduced or diminished in brain regions implicated in reward processing, addiction and other psychiatric conditions. We anticipate that these early changes in gene expression in response to drug exposure are likely to contribute to the consequences of prenatal exposure and their discovery might pave the way to therapeutic intervention to ameliorate the long-lasting deficits.